2020
DOI: 10.1002/smll.201906674
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilver Mitigates Biofilm Formation via FapC Amyloidosis Inhibition

Abstract: Multidrug resistance of bacteria is a major challenge due to the wide‐spread use of antibiotics. While a range of strategies have been developed in recent years, suppression of bacterial activity and virulence via their network of extracellular amyloid has rarely been explored, especially with nanomaterials. Here, silver nanoparticles and nanoclusters (AgNPs and AgNCs) capped with cationic branched polyethylenimine polymer are synthesized, and their antimicrobial potentials are determined at concentrations saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…Although metal effect to surface associated amyloids (SAFs) in biofilm matrix is yet scarcely studied 44,45 , we also hypothesized that high Zn concentrations might interfere with bacterial surface-associated amyloid [71][72][73][74] formation as it can negatively affect fibrillar structure of other amyloids [75][76][77][78][79] and could thereby disrupt SAF-mediated surface colonization. Although cell surface morphology seemed to differ between E. coli cells grown on nano-ZnO and uncoated surfaces in oligotrophic conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although metal effect to surface associated amyloids (SAFs) in biofilm matrix is yet scarcely studied 44,45 , we also hypothesized that high Zn concentrations might interfere with bacterial surface-associated amyloid [71][72][73][74] formation as it can negatively affect fibrillar structure of other amyloids [75][76][77][78][79] and could thereby disrupt SAF-mediated surface colonization. Although cell surface morphology seemed to differ between E. coli cells grown on nano-ZnO and uncoated surfaces in oligotrophic conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, proteins are one of the attractive targets for finding new antimicrobial therapies. To date, it has been shown that AuNPs and AgNPs, along with their respective ions, interact with several structural proteins, membrane proteins and several enzymes [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In an experimental and molecular docking study, Shah et al evidenced the diverse action of AgNPs on various proteins of Pseudomonas aeruginosa [ 32 ].…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
“…In this study, it is reported that several amino acids—leucine, aspartate, arginine, lysine, tyrosine, arginine, alanine and tryptophan—from active sites of the four proteins interact with AgNPs [ 33 ]. Structural proteins, such as bacterial amyloid FapC in P. aeruginosa , form a branched structure that helps in cell–cell adhesion, encasing dormant cells, QS, protection and biofilm integrity [ 34 ]. In a study done by Huma et al, AgNPs prevented fibrilization of FapC proteins by interacting with and sequestering FapC monomers ( Figure 3 B).…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomedicines and biomaterials have shown great promise in the treatment of various diseases in recent years [17][18][19][20]. To treat biofilm-associated infections, quorum sensing inhibitors [21,22], nanoparticles [23][24][25], antimicrobial peptides [26], antisense nucleic acids [27,28], enzyme mimetics [29], polymers [30][31][32] and antifouling coatings [33][34][35][36] with the activity of inhibiting biofilm formation were developed in the past decade. These compounds or materials could sensitize biofilm infections to conventional antibiotics [6,37].…”
Section: Introductionmentioning
confidence: 99%